Geographic variation in Trumpeter Swan Cygnus buccinator clutch size and egg weights - Olsen, Dave; Long, Bill; Mitchell, Carl D. (Wildfowl, 2015)
Because larger clutch sizes and heavier eggs may indicate fitness as well as resource availability, we investigated whether there were significant differences in clutch size and egg weights between the Interior Population (IP) and Rocky Mountain Population (RMP) of Trumpeter Swans Cygnus buccinator in North America. A total of 1,113 eggs were measured or weighed at 283 nests. Average clutch size ranged from 3.5–5.8 eggs across study sites, and average egg mass ranged from 333.25–373.80 g. Average clutch size was significantly larger for IP swans (5.8 eggs per clutch) than for those from the RMP (mean clutch size = 4.3 eggs). Egg weights were also significantly heavier in the IP (mean = 366.43 g) than in the RMP (mean = 336.98 g). Mean clutch sizes and egg weights were within the range of other studies involving Trumpeter Swans. The results may provide some indication why the IP is increasing at a faster rate than the RMP of Trumpeter Swans.